What information do general practitioners expect in letters from mental health services? - Nilforooshan, Ramin (London J Prim Care (Abingdon), 2009)
Background Psychiatrists and General Practitioners (GPs) communicate mainly by letters which often do not cover the necessary information. Setting Barnet PCT Question To identify what GPs regard as important and necessary information in psychiatric follow up letters. Method A postal questionnaire was sent to all GPs in the Borough of Barnet to determine their view on this matter. Results Out of 187 GPs, 129 responded to the questionnaire (69%). A mismatch was found between what psychiatrists write in their follow up letters and what GPs expect. Medication details, diagnosis, name of care coordinator and changes in mental state were considered very important to GPs. Conclusions Conveying information that GPs actually consider important may improve their ability to share care of mental health patients. This may be achievable by introducing standardised format letters.